ClimBeR Work Package III Technical Working Group Members Physical Meeting Report - Sarku, Rebecca; Nkanyani, Shiluva Chauke; Laichena, Joshua; Mavuso, Terrence; Whitfield, Stephen (University of Leeds, 2024)
This report is about the Challenge Climate variability and extremes are having significant, adverse impacts in low- and middle-income countries – and these impacts will only grow worse. Food and agricultural systems face particular risk, with threats of economic and employment losses and investment uncertainty. Smallholder farmers, and particularly women and youth, are vulnerable to setbacks in efforts to improve livelihoods, while poverty and social tensions grow. The demand has shifted from understanding climate change impacts to designing innovations and directing financial flows to achieve ambitious climate and food systems targets. Adaptation solutions must go beyond technology and consider social, environmental, and economic consequences as well — isolated interventions are no longer enough. Working to ensure transformation at the system level will enhance resilience, productivity, and equity. Working closely with partners at the local, national, regional, and global levels, ClimBeR’s bold and unique approach tackles vulnerability to climate change at its roots using a transformative adaptation framework.